The Comparative Policy Agendas Project: theory, measurement and findings*. (29th May 2015) - Dowding, Keith; Hindmoor, Andrew; Martin, Aaron
Abstract: The Policy Agendas Project (PAP) was developed in the United States in the early 1990s as a means of collecting data on the contents of the policy agenda. The PAP coding method has subsequently been employed in the United Kingdom, a number of European countries, Canada, Israel, New Zealand, as well as the state of Pennsylvania (http://www.comparativeagendas.org/ ). What does PAP measure? How does it measure it? What does it find? How does it explain what it finds? We use these questions to structure our review.